The first photometric investigation of two short-period Algol-type eclipsing binaries: IW UMa and V367 Gem - Tian, Xiao-Man; Jiang, Lin-Qiao; Wang, Zhi-Hua; Wang, Jing-Jing (Frontiers in Astronomy and Space Sciences, 2025)
IntroductionThe first multi-color photometric observations and low-resolution spectra of the Algol-type short-period eclipsing binary systems IWUMa and V367 Gem are presented here. The stellar atmospheric parameters of the primary stars were derived through spectral analysis. Ground-based and TESS-based light curves were analyzed.MethodsULySS software was employed to obtain atmospheric parameters by fitting full spectra with model spectra. Wilson–Devinney code was used to analyze the light curves.ResultsThe photometric solutions suggest that IW UMa and V367 Gem are both typical Algol systems in a semidetached configuration, with secondary stars filling their Roche lobes. The mass ratios of IW UMa and V367 Gem are 0.145 (3) and 0.478 (15), respectively. A third light was detected in the light curve analysis of V367 Gem with a luminosity contribution of L3/Ltotal=44.38%. Using O−C analysis, we found that the period of IW UMa is likely increasing over the long term, superposed with cyclic variation. The period of V367 Gem is decreasing at a rate of dP/dt=−7.40(± 0.43)×10−8d⋅yr−1 on a long time scale.DiscussionThe period decrease of V367 Gem may be due to the mass and angular momentum loss from the system. Additionally, a probable cyclic variation has been identified for the period of V367 Gem, which may be caused by the third body.